Godt – eller godt nok? Hvordan opplever sykepleiere idealer og realiteter i utøvelsen av yrket? - Christiansen, Bjørg; Bjørk, Ida Torunn (Nordisk tidsskrift for helseforskning, 2016)
Good work – or good enough? How do nurses perceive ideals and realities in the profession? The purpose of the study is to explore what it entails for nurses to perform good work. It may be challenging to maintain good work when demands of efficiency threaten professional and ethical ideals. How nurses describe expectations they set for themselves and others will also indicate their views on professional identity. The study is qualitative with a descriptive and explorative design, based on individual semi-structured interviews with eight nurses in specialist- and community health care. The data were analyzed in three different interpretational contexts, aiming at an insightful and valid understanding of the text. Findings show that good work was associated with responsible practice and a patient-centered approach. An obligation to update themselves is integrated into their professional identity. Findings show that we can no longer take for granted that nurses handle cross-pressures and value-conflicts in the profession.